Meta Analysis: The Soil Transmitted Helminth Infection and It’s Correlation with Anemia in Children - Nuryati, Arum (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
Soil-transmitted helminth (STH) infections are common in regions with high rates of anemia, particularly in low-income countries where poor nutrition is prevalent. Children attending school in these areas are most vulnerable to anemia. Both anemia and STH infections can negatively affect children's physical development, school attendance, and learning abilities. This study aims to examine the relationship between STH infections and anemia in children. A systematic review and meta-analysis following PRISMA guidelines were conducted. Articles were selected based on eligibility criteria defined using the PICO model: Population = Primary School Children, Intervention = STH infections, Comparison = No STH infections, Outcome = Anemia. The article search covered publications from 2002 to 2024 across databases such as PubMed, Science Direct, Google Scholar, Springer Link, Hindawi, and PLOS One. Keywords used included